Global Decline of Insects 2022
DOI: 10.5772/intechopen.102035
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Organic Farming on Insects Abundance and Diversity

Abstract: Organic farming encourages maximum utilization of the natural biological processes to manage the farm in terms of soil fertilization and pest control, which implies using none or less synthetic fertilizers, pesticides, and plant and animal growth-promoting substances. All these practices increase arthropod diversity, particularly soil-dwelling insects. Intercropping, cover crops, and hedges, which are common practices in organic fields, provide alternative habitats for arthropod communities. The refugia also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…This may be due to the availability of phosphorous and Nitrogen element, which stimulates and encourage the plant and regulates several vital activities the plant needs 25 . These results are in agreement with (5,26,27). Spraying of seaweed extracts resulted in no significant differences in the concentration of phosphorous in the leaves between the experimental treatments.…”
Section: The Concentration Of Phosphorous In the Leaves (%)supporting
confidence: 92%
See 2 more Smart Citations
“…This may be due to the availability of phosphorous and Nitrogen element, which stimulates and encourage the plant and regulates several vital activities the plant needs 25 . These results are in agreement with (5,26,27). Spraying of seaweed extracts resulted in no significant differences in the concentration of phosphorous in the leaves between the experimental treatments.…”
Section: The Concentration Of Phosphorous In the Leaves (%)supporting
confidence: 92%
“…The results of Table (5) showed that the addition of organic fertilizer led to a significant increase in the sulfur concentration in the fruits, which amounted to 1.96 and 2.00 mg sulfur kg -1 for the two treatments M2 and M3 (10 and 5% of the terracing volume) compared to the unfertilized treatment M0, which amounted to 1.611 mg sulfur kg -1 for the two treatments consecutively, with an increase of (25.49%).…”
Section: Sulfur Concentration In Fruits (Mg -1 Kg Sulfur)mentioning
confidence: 99%
See 1 more Smart Citation